IL-10 and NOS2 modulate antigen-specific reactivity and nerve infiltration by T cells in experimental leprosy. - Deanna A Hagge; David M Scollard; Nashone A Ray; Vilma T Marks; Angelina T Deming; John S Spencer; Linda B Adams (Public Library of Science (PLoS), 2014)
Although immunopathology dictates clinical outcome in leprosy, the dynamics of early and chronic infection are poorly defined. In the tuberculoid region of the spectrum, Mycobacterium leprae growth is restricted yet a severe granulomatous lesion can occur. The evolution and maintenance of chronic inflammatory processes like those observed in the leprosy granuloma involve an ongoing network of communications via cytokines. IL-10 has immunosuppressive properties and IL-10 genetic variants have been associated with leprosy development and reactions.The role of IL-10 in resistance and inflammation in leprosy was investigated using Mycobacterium leprae infection of mice deficient in IL-10 (IL-10-/-), as well as mice deficient in both inducible nitric oxide synthase (NOS2-/-) and IL-10 (10NOS2-/-). Although a lack of IL-10 did not affect M. leprae multiplication in the footpads (FP), inflammation increased from C57Bl/6 (B6)<IL-10-/-<NOS2-/-<10NOS2-/-. While IL-10-/- mice exhibited modest FP induration compared to B6, NOS2-/- and 10NOS2-/- mice developed markedly enlarged FP marking distinct phases: early (1 month), peak (3-4 months), and chronic (8 months). IFN-γ-producing CD4+CD44+ cells responding to M. leprae cell wall, membrane, and cytosol antigens and ML2028 (Ag85B) were significantly increased in the evolved granuloma in NOS2-/- FP compared to B6 and IL-10-/- during early and peak phases. In 10NOS2-/- FP, CD4+CD44+ and especially CD8+CD44+ responses were augmented even further to these antigens as well as to ML0380 (GroES), ML2038 (bacterioferritin), and ML1877 (EF-Tu). Moreover, fragmented nerves containing CD4+ cells were present in 10NOS2-/- FP.The 10NOS2-/- strain offers insight on the regulation of granuloma formation and maintenance by immune modulators in the resistant forms of leprosy and presents a new model for investigating the pathogenesis of neurological involvement.